A Student-Run Free Mobile Veterinary Clinic in the Phoenix Metropolitan Area - Molly Wozniak; Cortney Stablein; Nikalette Zuk; Rachael Kreisler (Journal of Student-Run Clinics, 2018)
For many individuals who are housing insecure or homeless, dealing with the emotional toll of these stressors is made more bearable by the companionship of a pet. However, access to veterinary care is limited for these and other underserved populations. To ensure veterinary care is made available for all pets, the Midwestern University College of Veterinary Medicine’s mobile veterinary clinic provides free veterinary services. Additional goals of our student-run free mobile veterinary clinic are to provide clinical and interprofessional opportunities for students, including education in the One Health initiative, and to expose students to the challenges associated with providing veterinary care to underserved populations. This article describes the clinic operations, impact, and future directions of the Midwestern University College of Veterinary Medicine’s mobile veterinary clinic.